2011
DOI: 10.1103/physrevb.83.174419
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy spin dynamics in the[YPc2]0

Abstract: 1 H nuclear magnetic resonance (NMR) measurements in [YPc2] 0 , an organic compound formed by radicals stacking along chains, are presented. The temperature dependence of the macroscopic susceptibility, of the NMR shift and of the spin-lattice relaxation rate 1/T1 indicate that the unpaired electron spins are not delocalized but rather form a S = 1/2 antiferromagnetic chain. The exchange couplings estimated from those measurements are all in quantitative agreement. The low-energy spin dynamics can be described… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…An overview of the molecular orientation reported on various substrates can be found in Table 2. 42 For single-decker phthalocyanines, optical lab based methods, such as variable angle spectroscopic ellipsometry, were already many times successfully applied for the determination of the average molecular orientation on various substrates, including opaque substrates, and it was demonstrated that the results are in good agreement with synchrotron based methods like NEXAFS. These observations are in line with studies of planar phthalocyanine molecules on various metallic substrates, indicating that the interaction between the highest energetic occupied  orbital of the ligand and the substrate governs the molecular orientation of the first layer and the intermolecular interaction determines the orientation in thicker films.…”
Section: Molecular Orientation Of Tbpc 2 On Different Substratesmentioning
confidence: 99%
“…An overview of the molecular orientation reported on various substrates can be found in Table 2. 42 For single-decker phthalocyanines, optical lab based methods, such as variable angle spectroscopic ellipsometry, were already many times successfully applied for the determination of the average molecular orientation on various substrates, including opaque substrates, and it was demonstrated that the results are in good agreement with synchrotron based methods like NEXAFS. These observations are in line with studies of planar phthalocyanine molecules on various metallic substrates, indicating that the interaction between the highest energetic occupied  orbital of the ligand and the substrate governs the molecular orientation of the first layer and the intermolecular interaction determines the orientation in thicker films.…”
Section: Molecular Orientation Of Tbpc 2 On Different Substratesmentioning
confidence: 99%
“…On the basis of these results for the CF level splitting it is possible to analyze the temperature (T) dependence of muon spin-lattice relaxation rate in the presence of an applied field, derived from previous µSR measurements performed at the ISIS facility 12 and from new measurements performed at the Paul Scherrer Institute (PSI). Accordingly, the spinphonon couplings driving the transitions among the CF levels have been derived and the characteristic correlation time for the spin fluctuations estimated.…”
Section: Introductionmentioning
confidence: 99%
“…pNMR plays a central role in the elucidation of the quantum dynamics of single-molecule magnets and antiferromagnetic spin rings [3]. Moreover, it is an increasingly central technique for probing strong spin-orbit coupled electronic states in a dissipative environment, as shown by a recent study of quantum tunneling processes [4], silent in ac-susceptibility experiments, in lanthanide-based (Dy 3+ and Tb 3+ ) molecular nanomagnets.…”
mentioning
confidence: 99%